A new atypical antipsychotic: quetiapine-induced sexual dysfunctions - Atmaca, M; Kuloglu, M; Tezcan, E (Springernature, 2005)
In this paper, we evaluated the new antipsychotic, quetiapine- induced sexual dysfunctions (SDs). The study group consisted of 36 patients with schizophrenia receiving quetiapine. The changes in general sexual functions were assessed by using Arizona Sexual Experience Scale (ASEX) and Udvalg for Kliniske Undersogelser (UKU) Side Effect Rating Scale at baseline and week 4. Also, prolactin (PRL) values were determined at baseline and week 4. There was statistically significant difference with respect to the mean ASEX score at week 4 compared with baseline. The most frequent SD was diminished libido in both male (31.8%) and female subjects (28.6%). No significant correlation was found between ASEX scores and PRL values. The results suggest that SDs are an important problem using even novel antipsychotic, quetiapine.
Keywords: quetiapine; antipsychotic; sexual dysfunction